Management of Post-Operative Pain and Quality of Life of Total Knee Arthroplasty Patients: A Prospective Study - Tamilselvan, T.; Rajasree, S.; Vineetha, S.; Alocious, Arya (Challenges and Advances in Pharmaceutical Research Vol. 5, 2022)
This study aims to evaluate pregabalin's impact on post-operative pain control and osteoarthritis (OA) patients' quality of life (QOL) following total knee arthroplasty. This prospective observational study was carried out at the orthopaedics department. Two groups of 96 patients each were created. Nonsteroidal anti-inflammatory drugs (NSAIDs) are used to treat 50 patients in Group A, while pregabalin is used to treat 46 patients in Group B. The visual analogue scale (VAS) and knee injury and OA outcome score (KOOS) questionnaires were administered to the study participants once every 60 days over the course of six months. By comparing the follow-up score to the baseline score, the treatment's impact was evaluated. Nonsteroidal anti-inflammatory drugs (NSAIDs) are often considered to be the preferred first-line treatment for OA. The study's findings revealed that the pain score of Group Bin VAS at the end of the study was2.56±0.34 and the KOOS pain score was 92.73±3.45 (p<0.01). The QOL score was improved significantly to 81.56±5.29 (p<0.01) as compared to Group A. The research found that pregabalin with NSAIDs group patients showed a better improvement in pain, symptoms, and QOL within a short duration as compared to NSAIDs alone used group